THE USE OF SCIENTIFIC AND LEGAL RESEARCH IN CRIMINAL PROCEEDINGS - Babikov, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study various aspects of the use of specialised knowledge in criminal proceedings, in particular, scientific conclusions, expert opinions, scientific and legal conclusions, and responses to information requests. Based on the case law, the author draws conclusions regarding the possibility of using various forms of specialised knowledge in criminal proceedings. Research methods: are conditioned by the stated purpose and include: dialectical, comparative legal, dogmatic, empirical, epistemological, comparative, systemic, structural and functional, and others. Results: the reform of the legal system of Ukraine in terms of procedural legislation and the use of various forms of specialised knowledge has necessitated the involvement of experts with specialised knowledge in order to ensure the most effective protection of constitutional rights and freedoms. The CPC of Ukraine has formulated restrictions in terms of conducting an expert examination to clarify issues of law, and does not express any reservations regarding the possibility of experts to study legal issues that are not within the competence of the court. At the same time, by providing conclusions on various legal issues, explanations for interpreting legislation and resolving conflicts, the expert does not determine the guilt of a person, the degree of punishment, but only helps the court to objectively and fully investigate the circumstances of the case from various aspects that are not available to the parties to the criminal proceedings and the court. The need to use specialised knowledge of specialists and legal experts is also recognised by the highest court, and such opinions are used in the course of consideration of specific proceedings. Discussion: given that in practice, the opinions of experts and legal specialists are actually used by the parties to criminal proceedings and the court, and such use is consistent with the guarantees of the right to a fair trial and, accordingly, the principles of criminal justice, criminal procedural legislation should be improved in terms of determining the grounds, conditions and limits of legal expertise.